Formulation of cosmetic serum from bamboo vinegar / Zizie Izzatie Mohamad Musa - Mohamad Musa, Zizie Izzatie (2024)
This research focuses on implementing the potential of bamboo vinegar (BV) into developing an eco-friendly and natural cosmetic serum that addresses the growing need for sustainable skincare products. BV is a byproduct of bamboo pyrolysis, and it has been recognized for its antioxidant and antimicrobial properties, making it a potent active ingredient in cosmetic formulation. This research aims to determine the optimum BV formulation that maximizes benefits while retaining stability and compatibility by evaluating the serum's texture, color, and odor to ensure user satisfaction. Despite the well-known benefits of BV that could be advantageous as an active ingredient, research on its applications remains limited. Therefore, the preparation of cosmetic serums containing BV involving five formulations utilizing the oil-in-water (O/W) emulsification process were studied. The GC-MS analysis of BV revealed 17 components, the most significant of which are phenol, 2-methy-, phenol, 2-4-dimethyl, and phenol, 4-methoxy-3-methyl. The BV had substantial antioxidant capabilities, with the maximum total phenolic content and DPPH radical scavenging activity found at 200 and 250 ppm, respectively. Antimicrobial testing showed specific antibacterial activity against E. coli and S. aureus. The combination of 1 % BV and 8% HA (F4) was appropriate for creating a balanced cosmetic serum with great skin compatibility, stability, and efficacy. Over three months, the prepared serum remained stable and homogeneous, demonstrated significant antioxidant activities, and provided modest sun protection with an SPF of 9.993. Furthermore, F4 showed appropriate antibacterial activity, especially against S. Aureus, making it a suitable choice for skincare applications. Thus, a serum containing BV was developed to enhance its benefits while maintaining stability and compatibility with other components. This composition targets skincare concerns such as acne treatment and antioxidant protection. Future research should focus on BV's antioxidant properties, its sun protection capabilities, and synergistic interactions with other natural antimicrobials to improve efficacy. Comprehensive stability studies will assure the BV cosmetic serum's long-term safety and efficacy.